Effect of general anesthesia vs. local anesthesia and collateral status on outcomes in anterior circulation occlusion - Chen, Guojie; Chen, Rundong; Gao, Tianxiang; Wang, Lijun; Xu, Hongye; Yin, Wen; Gao, Yu; Zhang, Lei; Zhang, Yongxin; Xing, Pengfei; Yang, Pengfei; Li, Zifu; et al. (Frontiers in Neurology, 2025)
Background and objectivesThe impact of anesthesia type on outcomes following endovascular thrombectomy (EVT) remains controversial. Collateral status assessed through perfusion imaging may provide critical insights for optimizing anesthesia strategies during EVT.MethodsIn this retrospective cohort study, functional outcomes after EVT (measured by the modified Rankin Scale score) were compared between general anesthesia (GA) vs. local anesthesia (LA) using a propensity score-matched model. The association between the hypoperfusion intensity ratio (HIR, defined as Tmax > 10s/Tmax > 6 s) and outcomes was evaluated through weighted multivariate logistic regression, with potential non-linearity explored using restricted cubic spline (RCS) regression. To validate the findings, five analytical approaches were applied, including propensity score matching, multivariate logistic modeling adjusted for all covariates, inverse probability of treatment weighting (IPTW), and doubly robust estimations with and without adjustments for unbalanced covariates.ResultsA total of 702 patients were included, with 327 (46.6%) receiving GA and 375 (53.4%) receiving LA. Propensity score matching achieved balanced baseline characteristics (p > 0.05). Among patients with good collateral status (HIR <0.4), GA was associated with worse functional outcomes (mRS 0–2: 49% vs. 70%; OR 2.88, 95% CI: 1.29–6.43). In patients with poor collateral status, outcomes were comparable between GA and LA (mRS 0–2: 50% vs. 59%; OR 1.73, 95% CI: 0.92–3.27). All five statistical models yielded consistent results.ConclusionsThere is an association between general anesthesia and poorer functional prognosis in patients with well-developed collateral circulation after endovascular thrombectomy (EVT). HIR may serve as a useful marker for anesthesia selection and triage in EVT.Classification of evidenceThis study provides Class III evidence that use of GA is associated with worse functional outcome in patients with good collateral that undergoing EVT.